The Improvement of Cognitive-Motor Function Scores Using the NIH-Toolbox in Adults Subjects After Biofield Energy Therapy: A Randomized Controlled Double-blind Trial - Trivedi, Dahryn; Trivedi, Mahendra Kumar; Branton, Alice; Mondal, Sambhu; Jana, Snehasis (Alternative therapies in health and medicine, 2024)
There is a growing interest for the use of an alternative treatment approach like biofield energy therapy for managing various diseases. However, the effectiveness of distance mode of biofield energy therapy on neuropsychological function has not been examined so far. The study was aimed to evaluate the effect of biofield energy therapy via distant mode for the benefits of neuropsychological functions in adult subjects. It comprised of three parallel groups (control, sham control, and biofield intervention). The cognitive-motor functioning scores were monitored using NIH-Toolbox in 119 adult subjects on day 0, day 90, and day 180. Double-blind, single-center, randomized controlled trial (RCT). Adult human subjects (male and female) with one or more psychological symptoms. Biofield energy therapy through distant/remote (virtual) mode. The cognitive-motor functioning scores. The cognitive-motor functioning scores were significantly improved in the biofield intervention group compared to the control and sham control groups: cognition- language (P < .0057 to P < .0001), working memory (P < .0001), episodic memory function (P < .0369 to P < .0001), and executive function (P < .0386 to P < .0029); motor- locomotion P < .0001), standing balance (P = .0144 to P = .0019), dexterity (P = .0474 to P < .0001), grip strength (P = .0132 to P = .0078) and endurance (P = .0041 to P = .0004). No adverse effects were observed throughout the study. Physical vital signs and blood parameters were within the normal ranges during the entire study period. Overall, cognitive and motor functions significantly improved in the blessing intervention group compared to the naïve control and sham control groups, which ultimately improved the neuropsychological function and quality of life in adult subjects.